Employers' organizations & HIV/AIDS in formation, tools and good practices for workplace action against HIV/AI DS - International Labour Office (Geneva : International labour Office, 2006)
Gives basic information about HIV and AIDS and its implications for society as a whole as well as for the world of work.
System requirements: Adobe reader, Windows 9x, NT/2000/XP, macintosh & Unix platforms.
English, Spanish and French
Keywords: AIDS (Disease) -- Prevention; Occupational health services